Osteoradionecrosis of the Temporal Bone Leading to Cerebellar Abscess - Thomas B. Layton (Case Reports in Otolaryngology)
Squamous cell carcinoma of the temporal bone is a rare and destructive malignancy and represents both diagnostic and therapeutic challenge. The complex regional anatomy of the temporal bone requires equally intricate surgical techniques to adequately resect the tumour mass during surgical excision. Adjuvant radiotherapy is offered to patients with advanced disease and has been showed to confer a survival benefit in carefully selected patients. One feared complication of radiotherapy is osteoradionecrosis and is a major obstacle faced in the treatment of head and neck cancers. The case presented here is a rare example of a patient who was successfully treated for SCC of the temporal with both surgical resection and adjuvant radiotherapy who subsequently developed two major complications: first, osteoradionecrosis of the temporal bone that leads to penetrating osteomyelitis; second, the formation of a large cerebellar abscess that required surgical drainage. This case is a rare example of the complications that are possible following radiotherapy to the head and the close follow-up that is required in patients.